ASSESSMENT OF NATURAL REGENERATION OF DIFFERENT FORMS OF GAPS IN ATRUSH FOREST - muzahim younis; Mohammed Al-alaaf; Mohanad Abd-Alqader (Mesopotamia Journal of Agriculture)
Atrush Forest is a mixed forest that contains many types of forest trees and shrubs, and the dominant species in these forests (Pinus brutia Ten., Querecus sp., Crataqus ozaralus, Juniperus oxycedrus, Rhus coriaria, Prunus amycdalus, Ficus carica L. and Plautus spina- christi), the total area of the study area was determined (126.1821) hectare, (1786) gaps were fixed, classified into four categories, measurements were taken of the crowns and the total height of the surrounding trees that make up the circumference of the gap. As for the gap area, use the ellipse formula. It was found that the numbers of small gaps come in the forefront for each category (X < 200) m2  and (200 < X < 400) m2 where the number of gaps in the first category (X < 200) (855) was a problem gap of 48% of the total  gaps, while the second category followed (200 < X < 400), in which the number of gaps was (444) gaps and constituted (25 %), while the third category (400 < X < 600), the number of gaps was (171) gaps formed by that (10%) of the total gaps, while the number of gaps in the fourth and large category (X > 600) was (316) gaps, and 17% of the total gaps formed, while the shapes for the gaps were the triangular, oval, regular, and irregular shape Regular proportions (6, 30, 37 and 27 %) respectively, and that the ellipse and regular form (67 %) of total space. As for the gaps with areas (400 < X < 200) m2 where the triangular, oval, regular and irregular shapes form the proportions (9, 28, 39, 24 %) respectively, we find that the oval and regular forms are a total of (67 %) of the areas of the second category, while the gaps with areas (600 < X < 400) m2 , the triangular, oval, regular and irregular shapes formed the proportions (13, 25, 40, 22 %) respectively, and the oval and regular forms formed 65% of the areas of the third category. While we find that the large gaps whose area is greater than (600 > X) m2, we find that the triangular, oval, regular and irregular oval shapes formed proportions (13, 18, 53, 16 %), respectively, and that the sum of the ratios The oval and regular forms of the fourth area category are (71 %), and this indicates that the oval and regular forms are the most common forms in the gaps, and there is no doubt that regular forms are prevalent at the site of the study and formed (17 %) of the total gaps.